1994
DOI: 10.1038/bjc.1994.59
|View full text |Cite
|
Sign up to set email alerts
|

Cancer morbidity in alcohol abusers

Abstract: Summary Data on the association between alcohol abuse and cancer morbidity are scarce in large cohorts of non-hospitalised alcoholic men and women. Of 18,368 alcohol abusers who entered an outpatient clinic in Copenhagen during 18,307 were followed and their cancer incidence was compared with that of the total Danish population. On average the 15,214 men were observed for 12.9 years and the 3,093 women for 9.4 years. The overall morbidity of cancer was increased significantly. Of the men, 1,441 developed canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 62 publications
3
55
0
Order By: Relevance
“…In the present investigation, there was a positive, dose-responsive relationship between alcohol consumption and HSIL risk and this has been supported by other studies [44]. Smoking was also positively associated with HSIL risk and this is also consistent with previous studies [45].…”
Section: Discussionsupporting
confidence: 82%
“…In the present investigation, there was a positive, dose-responsive relationship between alcohol consumption and HSIL risk and this has been supported by other studies [44]. Smoking was also positively associated with HSIL risk and this is also consistent with previous studies [45].…”
Section: Discussionsupporting
confidence: 82%
“…A cohort study of more than 3,000 Danish women in treatment for alcohol abuse followed for a mean of 9.4 years found no increased risk of endometrial or ovarian cancer, compared with the entire female Danish population. 221 A similar Swedish study also found no association. 222 In addition, a populationbased cohort study 223 and a number of case-control studies [224][225][226][227][228] have found no significant adverse association between relatively low-level alcohol consumption and endometrial cancer 224,[226][227][228] or ovarian cancer.…”
Section: Alcohol-related Consequences Unique To Womenmentioning
confidence: 64%
“…The Danish cohort study mentioned above observed an increased risk of cervical cancer in women treated for alcohol-related problems (RR 2.0; 95% CI 1.2, 3.0) compared with the general Danish population. 221 A similar Swedish retrospective cohort study also found an association between cervical, vaginal, and vulvar cancers in women registered with temperance boards. 222 However, both these studies, and another smaller one reporting a similar association, 232 were unable to control for known risk factors for cervical cancer or rates of Pap screening.…”
Section: Alcohol-related Consequences Unique To Womenmentioning
confidence: 86%
“…However, owing to small case numbers, previous prospective studies have typically collapsed cancers of the head and neck and the aesophagus into a single broad category of upper-gastrointestinal tract sites (Gronbaek et al, 1998;Kjaerheim et al, 1998;Boeing, 2002). Few prospective studies have examined the association between alcohol and individual head and neck cancer sub-sites, such as the larynx, oral cavity, or pharynx (Schottenfeld et al, 1974;Boffetta and Garfinkel, 1990;Adami et al, 1992;Tonnesen et al, 1994;Sigvardsson et al, 1996;Boffetta et al, 2001). Most of these studies have not adjusted for tobacco use, an important potential confounder of the relation between alcohol and head and neck cancer (Boffetta and Garfinkel, 1990).…”
mentioning
confidence: 99%